Elaboración del plan de mantenimiento preventivo para un motor eléctrico trifásico de 4 kW y 1500 rpm con arrancador estrella – triángulo (2023)
In terms of mechanics, control and maintenance of electric motors, the need to design a strategic plan that contributes to the improvement of the processes corresponding to the surveillance and prevention of this type of machinery in order to make its operation more efficient and safe has been raised. Along these lines, in this preliminary project, the development of a maintenance plan is proposed, particularly on threephase electric motors of 4kw and 1500 rpm with the stardelta starting mode, this, through the specific analysis of its own operating processes with the in order to generate a safe methodological structure in a preventive manner.